2020
DOI: 10.12691/jfnr-8-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-assisted Extraction, Purification, Antioxidant and Antibacterial Activity of Polysaccharide from <i>Cornus officinalis</i> Leaves

Abstract: The ultrasonic-assisted extraction process of polysaccharide from Cornus officinalis leaves (COLP) was optimized. After isolation and purification, the antioxidant and antibacterial activities of polysaccharide were studied in vitro. The extraction rate was highest under conditions of ultrasonic power 340 W, solvent to solid ratio 26:1(v/w), extraction temperature 71 °C and extraction time 2.3 h, reaching 7.04%, which was consistent with the model predicted value. The crude polysaccharide was isolated and puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Box–Behnken experimental design was applied to Design-Expert V8.0.6 software to determine the suitable process parameters for ultrasound-assisted extraction of PLP by response surface test analysis with PLP yield as the response value [ 24 , 25 ]. Experimental factors and level design are shown in Table 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The Box–Behnken experimental design was applied to Design-Expert V8.0.6 software to determine the suitable process parameters for ultrasound-assisted extraction of PLP by response surface test analysis with PLP yield as the response value [ 24 , 25 ]. Experimental factors and level design are shown in Table 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The isolated polysaccharide fractions demonstrated robust antioxidant activity by effectively scavenging DPPH, hydroxyl, and superoxide anion radicals. Additionally, they exhibited antibacterial efficacy against Salmonella typhimurium , Bacillus subtilis , Escherichia coli , and Staphylococcus aureus ( 102 ).…”
Section: Bioactive Compounds In Cornus Officinalismentioning
confidence: 99%
“…The fruit of Cornus officinalis is rich in iridoid glycosides, flavonoids, polyphenols, tannins, polysaccharides, and other active components [1] , and the polysaccharides are one of the most abundant active components in Cornus officinalis fruit. Mounting evidences have indicated that Cornus officinalis polysaccharides (COPs) have many bioactivities, such as antioxidant, anti-tumor, anti-inflammatory, anti-microbial, and anti-thrombotic activities [2] , [3] . The extraction of polysaccharides is the most critical step for its development or application.…”
Section: Introductionmentioning
confidence: 99%